Development and Sustainability India in a Global Perspective - Banerjee, Sarmila; Chakrabarti, Anjan; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2013)
Following the reforms undertaken in the last two decades, India’s economic landscape has been radically transformed. This book examines the new economic map, which is shown to be shaped by two intertwined currents: globalization and sustainability. Weaving extensively through these currents and the canvas of development in the Indian economy they open up, this work seeks to introduce new methodologies, a corpus of concepts and modes of analysis to make sense of the emerging order of things. What transpires in the course of the investigation is a critical reflection of the present in which not only the new institutions, policies and practices are analyzed, but their limitations, fragility and at times myopic approaches are brought to light. By highlighting the rough edges created by the new conditions, this book is firmly engaged with the frontier of the Indian economy and ends up challenging many well-known conjectures and assumptions. In doing so, it strives to shift the Indian economy to a new terrain, thereby fundamentally re-locating and re-orienting the discourse of that economy as a unique object of analysis.
Chapter 1: Introduction -- Chapter 2: Rethinking and Theorizing the Indian State In the context of New Economic Map -- Chapter 3: Global Financial Crisis: What Did We Know, What Have We Learnt? -- Chapter 4: Volatility, Long Memory and Chaos: A Discussion on some “Stylized Facts” in Financial Markets with a focus on High Frequency Data -- Chapter 5: Globalization and Labour Markets -- Chapter 6: Production Performance of Indian Agriculture In the Era of Economic Reforms -- Chapter 7: Under the Shadow: Pricing and Marketing in Indian Agriculture in Globalisation -- Chapter 8: Promoting Entrepreneurship among Women in Agriculture -- Chapter 9: Construction & Engineering Industry of India in PPP Regime With a Special Focus on Airport Development -- Chapter 10: Performance Evaluation Techniques: An Application to Indian Garments Industry -- Chapter 11: Telecommunications Industry in the Era of Globalization with Special Reference to India -- Chapter 12: Market Structure of Crude Steel Industry and India’s Position in the Era of Globalization -- Chapter 13: Nabadiganta - A new horizon? Patriarchy, Globalization and women’s agency in the IT sector -- Chapter 14: Dualism in the Informal Economy: Exploring the Indian informal manufacturing sector -- Chapter 15: Indian Gems and Jewellery Industry: An Enquiry into the Nature of Competitive Advantage -- Chapter 16: On Assessment of Women Empowerment at Individual Level: An Analytical Exposition -- Chapter 17: Sustainable Poverty Reduction: Credit for the Poor -- Chapter 18: Employment Guarantee and Natural Vulnerability: A Study of MGNREGA in Indian Sundarbans -- Chapter 19: Inequality, Public Service Provision and Exclusion of the Poor -- Chapter 20: Stakeholder Attitudes and Conservation of Natural Resources: Exploring Alternative Approaches -- Chapter 21: Indoor Air Pollution and Incidence of Morbidity: A Study on Urban West Bengal -- Chapter 22: Efficient Pollution Management through CETP: The Case of Calcutta Leather Complex -- Chapter 23: Embracing the Global Knowledge Economy: Challenges facing Indian Higher Education -- Chapter 24: HIV Epidemic: Global Response and India’s Policy -- Chapter 25: The Political Economy of Mental Health in India.    .
Keywords: Development economics; Globalization; Markets; Economic growth; Economic policy; Environmental economics; Social policy; Development Economics; Emerging Markets/Globalization.; Economic Growth; Economic Policy; Environmental Economics; Social Policy